Symposium 10: A Critique of Participative Discourses Adopted in Networked Learning - Reyolds, Michael; Sclater, Madeleine; Tickner, Sue (Proceedings of the International Conference on Networked Learning, 2004)
The predominant discourse of e-learning is frequently focused on the adoption of participative learning approaches involving co-operation, collaboration and peer assessment incorporating implied principles of democracy and ‘community’. There are tensions in the practical application of these features, particularly in relation to working with ‘difference' when comparing the underlying course philosophy with student experience of such courses. There is an implicit assumption that being participative means sharing control but what, in practice, does this entail for the students? Different interpretations of participative approaches will be identified (pedagogical, ideological or both) and an illustrative case discussed in which the principle of participation was applied to the design and assessment of assignments.